Electrochemically fabricated pyrrole copolymer thin films and their electroactivity in neutral aqueous solution - Rapiphun Janmanee (2018)
The functionalized pyrrole copolymers were fabricated by electropolymerization of pyrrole (Py) and functionalized pyrrole monomers, pyrrole-3-carboxylic acid (P3C) and 4-(3-pyrrole) butyric acid (PBA). The electrochemical behavior and doping/dedoping properties of the obtained copolymer thin films were investigated by cyclic voltammetry (CV) in neutral phosphate-buffered saline (PBS) solution. Moreover, the functionalized pyrrole copolymer films were characterized by UV-vis absorption spectroscopy and atomic force microscopy (AFM). The obtained copolymer thin films showed good stability and electroactivity in neutral PBS solution. The presented functionalized pyrrole copolymer thin films may possess potential applications to study in various systems of the biosensors. © 2013 Taylor and Francis, LLC.